Distribution of Manganese in Soils of South-East Rajasthan - Mehra, R K; Baser, B L (Annals of Arid Zone, 2016)
Twenty eight samples from seven soil profiles of south-east Rajasthan (Udaipur district) were studied for different forms of manganese. They contained 385-945 ppm total, 44.9 - 227.2 ppm active, 41.5 - 224.2 ppm easily reducible, 3 - 7.3 ppm available, 1.7 - 6.2 ppm exchangeable and 0.75- 2.95 ppm water soluble manganese. Black soils contained more manganese than red soils. Both total and act ive manganese generally decreased with depth. Easily reducible, available and exchangeable forms of manganese decreased with depth and appear to be a function of pH (r=0.47, 0.79 and 0.65, respectively).Exchangeable manganese was found to be associated with clay content (r=0.42) and calcicum carbonate (r = 057). Water soluble manganese decreased with depth and clay (r=0.69) but increased with organic carbon (r=0.78).